Dementia in prison : an ethical framework to support research, practice and prisoners - Brooke, Joanne (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This innovative volume exposes dementia as a condition that the aging prison population is increasingly facing. Going beyond exploring the need to understand dementia within prison populations, it argues that healthcare workers and prison staff must ensure that prisoners developing dementia during their sentence are identified and supported. Dementia in Prison covers three key areas: Healthcare services in prison settings and how these affect the rapidly aging prison population, The human rights of prisoners with dementia, alongside the ethics of healthcare in this environment, The current state of support for prisoners with dementia and any recommendations for future assessment, diagnosis, and policies. This provocative book will be invaluable to scholars in the fields of public health, criminology and medical sociology as well as nurses and prison staff"--
OCLC-licensed vendor bibliographic record.
Keywords: Older prisoners -- United States; Older prisoners -- Medical care -- United States; Dementia -- United States; MEDICAL / Mental Health; MEDICAL / Public Health; SOCIAL SCIENCE / Criminology